Holistic learning study in the Pancasila Student Profile Strengthening Project (P5) in penggerak schools - Yuniati, Astuti; Marmoah, Sri; Suryandari, Kartika Chrysti (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2024)
Holistic learning has a significant role in overcoming global education problems. Holistic learning is learning that involves various aspects of students' intelligence. This learning is fundamental but has not been fully implemented in Penggerak Schools. The objectives of the study are (1) to describe the P5 learning plan, (2) to explore the implementation of P5 learning, and (3) to measure the results of P5 activities. The type of research used is qualitative with a case study approach. Data is collected through observation, interviews, and document content analysis. Meanwhile, data analysis uses collection, reduction, data presentation, and conclusion. The participants were the principal, six students, and three teachers of various phases at one of the private elementary schools. The results of the study show that (1) holistic learning planning includes planning the P5 project module, including determining themes, dimensions, and time allocation; (2) the application of holistic learning is carried out by paying attention to various multiple intelligences by developing spiritual, aesthetic, physical, intellectual, emotional, and social aspects, (3) measurement of P5 outcomes in holistic learning uses authentic assessment. The conclusion is that P5 activities at one of the private elementary schools in Klaten have fulfilled the holistic learning aspect. This study suggests that the government can make policies to implement holistic learning to improve the quality of education.